Identificação e fatores de virulência de Candida spp isoladas da cavidade bucal de transplantados renais do hospital universitário Onofre Lopes em Natal-RN - Diniz, Mariana Guimarães (2011)
Despite Candida species are often human commensals isolated from various oral sites such as: tongue, cheek and palatal mucosa plus subgingival region, there are some properties linked to the organism commonly known as virulence factors which confer them the ability to produce disease. Oral candidiasis is one of the main oral manifestations reported in literature related to kidney transplant patients. The objectives of the present study were to identify and investigate virulence factors of yeasts isolated from the oral cavity of kidney transplant recipients admitted at the Hospital Universitário Onofre Lopes, in Natal RN. Seventy Candida species isolated from 111 kidney transplant recipients were investigated in this study. Identification of the isolates was performed by using the evidence of germ tube formation, hypertonic broth, tolerance to grow at 42°C, micromorphology and biochemical profiles. We observed a high rate of isolation of yeasts from the oral cavity of kidney transplant recipients (63.1%) being C. albicans was the most prevalent species. Oral candidiasis was diagnosed in 14.4% of transplant recipients. We evaluated virulence properties of the isolates regarding to: biofilm formation on polystyrene microplates as well as XTT reduction, adherence to acrylic resin and human buccal epithelial cells and proteinase activity. Most isolates were able to form biofilm by the method of adhesion to polystyrene. All isolates of Candida spp. remained viable during biofilm formation when analyzed by the method of XTT reduction. The number of CFU attached to the acrylic resin suggested high adherence for C. parapsilosis. C. albicans isolates showed higher median adherence to human buccal epithelial cells than non-C. albicans Candida isolates. Nevertheless, this difference was not statistically significant. C. dubliniensis showed low ability to adhere to plastic and epithelial cells and biofilm formation. Proteolytic activity was observed for all the isolates investigated, including the unique isolate of C. dubliniensis. There was a statistically significant association between proteinase production and the presence of oral candidiasis. Studies related to oral candidiasis in renal transplant recipients are limited to clinical and epidemiological data, but investigations concerning Candida spp. virulence factor for this group of individuals are still scarce. We emphasize the importance of studies related to virulence factors of yeasts isolated from this population to contribute to the knowledge of microbiological aspects of oral candidiasis